Interaction of Unemployment, Socioeconomic Factors and Demographic Dividend in South Africa: Issues and Policy Options - Nkhumeleni, Mpho; Stiegler, Nancy; Ogujiuba, Kanayo (International Journal of Economics and Financial Issues, 2022)
Unemployment is a major barrier to achieving a successful demographic dividend in many countries, including South Africa. A shortage of skills and knowledge among the working-age population is one of the key issues. The objective of this article is to examine if there is a link between youth unemployment in South Africa and demographic indicators. This article examines the relationship between educational achievement and employment status among working-age South Africans. Secondary data was used, and desktop analysis was performed on the information gathered from the Quarterly Labour Force Survey of 2017 and 2019. Findings show a link between youth unemployment and demographic characteristics, as well as a link between educational attainment and work status in South Africa. According to our findings, when it comes to gender and employment possibilities, women have a harder time finding jobs than men. in addition, being black or African makes it more challenging to find a job compared to other demographic groups. This suggests that more must be done in the labor market for South Africa’s economy to grow. Youth labor force involvement must be increased in the future to reduce the number of discouraged job seekers. Government initiatives that promote labor market flexibility should be implemented.